2022
DOI: 10.1111/tme.12923
|View full text |Cite
|
Sign up to set email alerts
|

Residual risk estimates of transfusion transmissible hepatitis B, hepatitis C and human immunodeficiency virus using nucleic acid testing yield/window period model in an Indian setting

Abstract: Background Estimation of residual risk (RR) is necessary to understand status of blood safety with current testing strategies and need to improve it further. These estimates from India are lacking till date. Present study was aimed to estimate RR and incident rate (IR) of transfusion transmitted infectious disease (TTIDs) in Indian setting. Study Design and Methods Blood donor demographic data, serological testing results and nucleic acid testing (NAT) screening results were collected retrospectively from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results are comparable to a local study by Moiz et al in which the RR of HBV transmission was 1 in 10,900 donors, and for HCV, it was 1 in 13,900 donors [ 6 ]. These rates are relatively higher in India, as shown by Pandey et al in a recently published study; they found RR with NAT of 16.1 per million donors and 4.4 per million donors for HBV and HCV, respectively [ 13 ]. Studies from western countries like US and Canada show that the RR of transmission of HCV and HIV is lower than that of HBV [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are comparable to a local study by Moiz et al in which the RR of HBV transmission was 1 in 10,900 donors, and for HCV, it was 1 in 13,900 donors [ 6 ]. These rates are relatively higher in India, as shown by Pandey et al in a recently published study; they found RR with NAT of 16.1 per million donors and 4.4 per million donors for HBV and HCV, respectively [ 13 ]. Studies from western countries like US and Canada show that the RR of transmission of HCV and HIV is lower than that of HBV [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent China study reported that NAT yields were 1062.90 per million and 0.97 per million for HBV and HCV, respectively [ 23 ]. Another study from India also showed 74 HBV, 12 HCV, and 1 HIV NAT positive cases in 1033,22 first-time donors tested [ 13 ]. A detailed comparison of NAT yield reported in different studies is shown in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation